Mammies, brute Negroes, and white femininity in teacher education. Issue 5 (9th December 2020) - Miller, Erin; Lensmire, Timothy
Abstract: In this article, we examine two stories about white femininity. The first, written by Danielle, was an assignment in a pre-service teacher education course. The second story is of the fictional Lily—the main character of an internationally best-selling novel. In our analyses, we pay special attention to how enduring racist images and caricatures of black people function in the complex social construction of white femininity. We conclude that teacher education efforts in the United States are undermined by the workings and power of enduring racist stereotypes in the thinking, feeling, and action of white teachers.